2015
DOI: 10.21273/jashs.140.5.436
|View full text |Cite
|
Sign up to set email alerts
|

Genome Size and Ploidy of Phlox paniculata and Related Germplasm in Subsections Paniculatae and Phlox

Abstract: Phlox is an important genus of herbaceous ornamental plants previously targeted for germplasm development, characterization, and enhancement by the U.S. Department of Agriculture, National Plant Germplasm System. Among Phlox in cultivation, Phlox paniculata is the most widely grown and intensively bred species, but little is known about variation in genome size and ploidy of this species or of related taxa that may be used for germplasm enhancement. The objective of this study was to assess cytotype variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The crossing results presented here corroborate those of previous experiments involving these Phlox species (Levin, 1963, 1966; Levin & Smith, 1965; Zale, 2014): heterospecific crosses yielded fewer seeds than conspecific crosses, and crosses between species with different style lengths yielded seeds only when the pollen parent was long-styled. As in these previous experiments, we found that controlled crosses within a species often did not result in complete seed set.…”
Section: Discussionsupporting
confidence: 89%
“…The crossing results presented here corroborate those of previous experiments involving these Phlox species (Levin, 1963, 1966; Levin & Smith, 1965; Zale, 2014): heterospecific crosses yielded fewer seeds than conspecific crosses, and crosses between species with different style lengths yielded seeds only when the pollen parent was long-styled. As in these previous experiments, we found that controlled crosses within a species often did not result in complete seed set.…”
Section: Discussionsupporting
confidence: 89%
“…Prior work on P. amabilis identified populations with three ploidies: diploids, tetraploids, and hexaploids (Fehlberg and Ferguson, 2012a, b). Cytotypic variation in other species of Phlox L. is well documented (Flory, 1934; Meyer, 1944; Levin, 1966; Smith and Levin, 1967; Levy and Levin, 1974; Worcester et al, 2012; Zale and Jourdan, 2015; Wright et al, 2016; Zale et al, 2016). Moreover, morphological (Zhang et al, 2008; Tiwari and Mishra, 2012) and ecological (Garbutt and Bazzaz, 1983; Vyas et al, 2007) effects of polyploidy have been documented in synthetic polyploids of other species of Phlox .…”
mentioning
confidence: 99%
“…Phlox specimens are notoriously variable in appearance, even within populations (Zale 2014). Therefore, we tested the hypothesis that it was an F 1 hybrid by combining genetic and morphological measures.…”
Section: Introductionmentioning
confidence: 99%